THE IMPLEMENTATION OF ELECTRONIC-BASED SYSTEM IN REDUCTION OF MEDICATION ERROR: A LITERATURE REVIEW - Saho, Musa; Rr. Tutik Sri Hariyati; Hening Pujasari (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2024)
Medication errors have been a persistent issue in healthcare, often overshadowing nurses' ability to focus on patient care. Traditionally, nurses have devoted considerable time to calculating medications—dosages, routes, and frequencies—at the expense of other caregiving duties. This literature review explores the adoption of electronic-based systems to reduce medication errors and associated risks in healthcare settings. The research involved examining databases such as Clinical-key-nursing, Science Direct, ProQuest, Embase, and academic articles, using keywords like "medication error" and "electronic-based system." The findings suggest that electronic systems can mitigate harms linked to medication errors by ensuring compliance with the "10 rights of medication administration," which include the right patient, drug, dose, time, route, documentation, assessment, approach, drug interaction, and information. The review analyzed 19 articles, but only ten met the inclusion criteria. The results indicate a positive correlation between the use of electronic systems and a decrease in medication errors, highlighting the potential benefits of technology in enhancing patient safety and care efficiency.